Orgasmic birth: the anatomy of pleasure in childbirth - Pascali-Bonaro, Debra (Frontiers in Global Women's Health, 2025)
Contemporary childbirth practices, which have long been globally dominated by a biomedicalized framework, have sterilized the birthing experience, have stripped away emotional and physical pleasures as well as essential aspects of women's sexuality, and have led to a loss of autonomy for many women and birthing people. In this article, I propose an alternative model of care— “orgasmic birth”. And I explain that this model emphasizes respectful perinatal care, pleasurable births, and childbearers’ empowerment. By drawing on my reviews of the extensive scientific literature on hormonal interplays, the anatomies of pleasure, and sexuality, in this article, I also discuss how biomedical interventions such as synthetic hormones, epidural nerve blocks, and cesareans disrupt the natural hormonal flow that is associated with pleasurable births. The results of my literature reviews have shown that a more holistic, respectful approach to perinatal care can reduce pain, decrease birth traumas, and improve satisfaction by acknowledging the important roles of pleasure and sexuality during childbirth. I also strongly argue that future research should explore how biomedical systems can integrate practices that honor both safety and the potential for pleasure during childbirth.